Analysis of Students' Mathematical Understanding in Gradient Material Linear Function Graphics Class IX UPTD SMP Negeri 3 Pematang Siantar - Br Sitepu, Yesika Veronika; Pangaribuan, Firman; Simarmata, Gayus (EduMatika: Jurnal MIPA, 2023)
This research aims to find out how to analyze students' mathematical understanding of gradient materials for linear function graphs for Class IX 7 UPTD SMP Negeri 3 Pematang Siantar. The research method used in this research is a qualitative method with descriptive data analysis. The subjects in this research are all students in class IX 7 of SMP Negeri 3 Pematang Siantar in the 2023/2024 academic year. The number of subjects in this research was 30 students. The instrument used in this research is a mathematical understanding test in the form of a description using 3 indicators, namely restating concepts that have been studied, presenting concepts in various forms of mathematical representation, applying concepts or problem-solving algorithms. These 3 indicators are used in 6 questions. Based on the data analysis carried out, the overall mathematical understanding ability of students is at a medium level, namely with a percentage of 47.8%. The indicators used are 1) restating mathematical concepts, 2) presenting mathematical representations, 3) applying concepts or problem-solving algorithms. Based on the previous explanation, it can be concluded that the mathematical understanding of students in class IX 7 UPTD SMP Negeri 3 Pematang Siantar as a whole is at a medium level.